Teller, July 27, 1907 - Nowell, Frank H., 1864-1950 (1907)
Caption on image: Teller, Alaska, July 27th 1907. F.H. Nowell, Nome, 5534 Teller is located on a spit between Port Clarence and Grantley Harbor, 55 miles southeast of Cape Prince of Wales, Seward Peninsula. Originally called Nooke by the Eskimo people of the area, who used it for the purpose of catching and drying fish, this location was used in the winter of 1866-67 as quarters by Capt. Daniel Libby's section of the Western Union Telegraph Expedition and was known as Libbysville or Libby Station. It is doubtful that any permanent settlement was established here before 1900, when the village of Teller was founded after the Bluestone placers, 15 miles to the south, were discovered. The name was probably derived from the Teller Reindeer Station situated on the north shore of Port Clarence. (pg. 955) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number